Proceedings of the Fourth Ship Technology and Research (Star) Symposium, Houston, Texas, April 25-28, 1979 - Ship Technology and Research (STAR) Symposium (4th : 1979 : Houston, Texas); Society of Naval Architects and Marine Engineers (United States) (New York : SNAME, 1979)
19